Implementasi Peraturan Walikota - Situmorang, Lias Ate (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This study discusses the implementation of Mayor Regulation No.28 of 2020 Article 9 Paragraph (3) concerning Health Protocols in Padangsidimpuan City. This research is motivated by the fact that there are many people in Padangsidimpuan City who do not comply with the Health Protocol even though a Mayor Regulation has been issued and provides sanctions for violators of the Health Protocol. This type of research is field research, namely research conducted in the field aimed at obtaining information and describing events, events that have occurred in the field in accordance with the facts found. The results of the study stated that the implementation of Mayor Regulation No. 28 of 2020 Article 9 paragraph (3) concerning Health Protocols in Padangsidimpuan City has not been carried out properly, this can be seen from the number of people who do not comply with health protocols even though there is a Mayor Regulation that regulates Health Protocols. and will be subject to sanctions for those who violate these regulations. There are still sanctions in Mayor Regulation No. 28 of 2020 Article 9 paragraph (3) concerning Health Protocols that have not been applied to the community by health protocol officers so that some people are less concerned about the importance of health protocols.